Pemberdayaan Kelompok Setia Kawan dalam Produksi Garam Beryodium di Desa Labuhan Bajo, Sumbawa - Dedi Syafikri; Dwi Mardhia; Fahmi Yahya; Nining Andriyani (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Labuhan Bajo Village is one of the villages designated as a center for the development of community salt in Sumbawa Regency. Problem related to salt encountered in Labuhan Bajo Village is the low income of the salt farmers group, there is still need to increase the quality and quantity of salt production and the absence of iodized salt production. The other problem is related to iodine deficiency (IDD), such as the stunting case, which is need to be handled immediately, considering that Labuhan Bajo Village is one of the villages in Utan Subdistrict which has a high stunted prevalence (22.1%). Therefore this service is expected to be a solution for the availability of iodized salt production in Sumbawa, especially in Labuhan Bajo Village while contributing to stunted prevention. The aim of this service activity is to assist Setia Kawan group in increasing the quantity and quality of salt to KW 1 and producing iodized salt that meets SNI requirements. The method for carrying out this community service activity includes counseling, training, assistance in procurement of equipment and assistance. The results of this activity are the availability of salt processing technology using the TUF + Iodization method, increasing the amount of salt production by the Setia Kawan Group, the availability of KW 1 salt and iodized, increasing the income of the Setia Kawan group, increasing the marketing network and increasing the knowledge and skills of salt farmers in applying TUF + Iodization method.